Land Conversion of Bangka Tin Mining Company into Agricultural Land and Socio-Economic Impacts for The Surrounding Communities - Fauzan Syahru Ramadhan; Nur Ramadhani Catur Anggoro (Criksetra: Jurnal Pendidikan Sejarah, 2025)
This article focuses on the conversion of Bangka Tin Mining Company land into agricultural land and its impact on the community around the mine. The process of land conversion of the Bangka Tin Company into agricultural land is unique for several reasons, such as the mining area certainly does not have much flora and fauna ecosystem life because mining areas tend to be arid due to mining machines and mining waste and mining areas usually cause mining scars that are simply abandoned without reforesting the mining area. This article aims to find out the process of land conversion of the Bangka Tin Company into agricultural land and the impact of the land conversion on the surrounding community. The method used in preparing this article is the historical method. The historical method is carried out with four stages, namely heuristics, criticism, interpretation, and historiography. From this research, it is known that the land conversion of the Bangka Tin Mining Company into agricultural land initially caused conflict between the company and the surrounding community, but in the end it ended with an agreement between the two parties peacefully through the assistance of the Central Government.